Design and Anticipated Outcomes of the eMERGE‐PGx Project: A Multicenter Pilot for Preemptive Pharmacogenomics in Electronic Health Record Systems. Issue 4 (24th June 2014) - Rasmussen‐Torvik, L J; Stallings, S C; Gordon, A S; Almoguera, B; Basford, M A; Bielinski, S J; Brautbar, A; Brilliant, M H; Carrell, D S; Connolly, J J; Crosslin, D R; Doheny, K F; et al.
<x xml:space="preserve">Abstract</x> We describe here the design and initial implementation of the eMERGE‐PGx project. eMERGE‐PGx, a partnership of the Electronic Medical Records and Genomics Network and the Pharmacogenomics Research Network, has three objectives: (i) to deploy PGRNseq, a next‐generation sequencing platform assessing sequence variation in 84 proposed pharmacogenes, in nearly 9, 000 patients likely to be prescribed drugs of interest in a 1‐ to 3‐year time frame across several clinical sites; (ii) to integrate well‐established clinically validated pharmacogenetic genotypes into the electronic health record with associated clinical decision support and to assess process and clinical outcomes of implementation; and (iii) to develop a repository of pharmacogenetic variants of unknown significance linked to a repository of electronic health record–based clinical phenotype data for ongoing pharmacogenomics discovery. We describe site‐specific project implementation and anticipated products, including genetic variant and phenotype data repositories, novel variant association studies, clinical decision support modules, clinical and process outcomes, approaches to managing incidental findings, and patient and clinician education methods. Clinical Pharmacology & Therapeutics (2014); 96 4, 482–489. doi:10.1038/clpt.2014.137